Malignant fibrous histiocytoma of the right upper leg – A case report - Pavlovic, Mladen; Milošević, Bojan; Radovanović, Dragče; Cvetković, Aleksandar; Trifunović, Bratislav; Čanović, Dragan; Mitrović, Slobodanka; Jovanović, Milan; Spasić, Marko; Vulović, Maja; Stojanović, Bojan; Jeremić, Dejan; et al. (Vojnosanitetski pregled, 2020)
Introduction. Malignant fibrous histiocytoma is a fast spreading pleomorphic sarcoma with a high malignant potential. Its spreading is characterized with local invasion and distant metastazes with early onset. Most common localisations of development are extremities, trunk and retroperitoneum. Given the line of rare case and specimen, lack of a clear etiology and mechanisms of this disease, as well as adequate histopathologic findings and intraoperative documentation, we presented current status, discuss putative etiology, histopathology with variant morphology, differential diagnosis and treatment modalities. Case report. We presented  a 56-years-old female Serbian with tumor in the thigh that clinically resembles incapsulated hematoma. Computed tomography revealed intramuscular tumor with a heterodense structure and compression on surround tissue. Ex tempore biopsy specimen showed malignant potential of the tumor. Wide and radical excision of the nodule has been done, and definitive histopathological verification revealed malignant fibrous histiocytoma. Conclusion. Malignant fibrous histiocytoma is a most common type of soft tissue sarcomas in adults. Frequent localization is on lower extremities, and every rapidly enlarging nodule in this localization that on computed tomography is like incapsulated hematoma with necrotic zone should alert suspicion on presence of this type of sarcoma
Keywords: sarcoma; soft tissue neoplasms; diagnosis; histological techniques; surgical procedures, operative